Alkaline Enhanced-Separation of Waste Lubricant Oils from Railway Contaminated Soil - Park, Sung-Woo; Lee, Jae-Young; Kim, Kyung-Jo; Yang, Jung-Seok; Baek, Kitae (TAYLOR & FRANCIS INC, 2010)
A surfactant-enhanced washing process for the removal of waste lubricant oil from train station soil was investigated by performing batch and column experiments. Surfactants removed 24.8-29.1% of the lubricant oil from soil in batch system, while the removal was slightly lowered to 15.8-26.2% in the column experiment. Alkaline-enhanced surfactant washing increased the removal efficiency up to 52%, while the removal was 42% in alkaline soil washing. An alkaline solution enhanced the removal of lubricant oil from soil because of soap formation. Even though the alkali-enhanced surfactant washing/flushing process effectively removed the lubricant oil from the soil, the residual concentration still exceeded the Korean regulatory level. To meet that level, further research is needed to enhance the removal of the lubricant.